Analysis of The Heavy Metal Content of Copper (Cu) in The Sediments and Leaves of The Avicennia marina Mangrove in The Wonorejo Mangrove Ecotourism Area, Surabaya - Chandra Bagas Swastika Bagas; Prayogo; Boedi Setya Rahardja (Universitas Airlangga, 2023)
Mangrove plants have the ability to accumulate heavy metals and help reduce the concentration level of pollutants in water. Sediment and leaves of Avicennia marina have the potential to be indicators of the heavy metal copper content in an area. The aim of this research is to determine the content of the heavy metal copper in soil sediments and leaves of the Avicennia marina mangrove in the Jagir River and Avur River in the Wonorejo Mangrove Ecotourism Area. The research method used is a descriptive method with a field survey. Sampling was calculated starting from the Jagir River flow in the Wonorejo Mangrove Ecotourism area (points A1, A2, A3) and the Avur River flow in the Wonorejo Mangrove Ecotourism area (points B1, B2, B3). Analysis of heavy metals in samples using Atomic Absorption Spectrophotometry (AAS). The test results showed that the highest content of the heavy metal copper (Cu) in the sediment and leaves of Avicennia marina Jagir River were 21.05 ppm and 16.10 ppm respectively. The highest content of the heavy metal copper (Cu) in the sediment and leaves of Avicennia marina in the Avur River in the Wonorejo Mangrove Ecotourism Area, Surabaya is 20.50 ppm and 17.10 ppm. The correlation coefficient for sediment and leaves of Avicennia marina in the Jagir River is 0.822 and in the Avur River is 0.829. The correlation between sediment and Avicennia marina leaves is positive with a very strong correlation.